A study on the efficiency and stability of different categories of banks in Malaysia - Sulong, Zunaidah; Yahya, Mohamed Hisham; Mohd Salleh, Zanariah (Universiti Sains Islam Malaysia, 2020)
This paper aims to gain new insights on efficiency and stability in a dual banking system. It evaluates the efficiency level and stability performance of two types of bank operating in Malaysia, i.e. conventional and Islamic, between 2012 to 2017. The data was extracted from Central Bank of Malaysia (BNM) and annual reports of individual banks. Z-score and data envelopment analysis (DEA) were employed to evaluate bank efficiency and stability, respectively. T-test and panel data regression were used in determining the disparity in stability performance. Interestingly, the results reveal different impacts of efficiency and stability on both types of banking system. It is found that conventional banks are less likely to experience bankruptcy and have better financial health. The Islamic banks, however, are found to be inefficient and more unstable compared to conventional banks. The results suggest that Islamic banks need to capitalize the effect of leverage, cost and production efficiency and economies of scale.